2007
DOI: 10.1177/1359105307078170
|View full text |Cite
|
Sign up to set email alerts
|

Stigma, Concealment and Symptoms of Depression as Explanations for Sexually Transmitted Infections among Gay Men

Abstract: This study examined how perceived sociocultural factors influenced the relationship between psychosocial variables and sexually transmitted infections (STIs) among gay men. A cross-sectional brief street-intercept survey was administered to 594 gay men. Analyses examined how well stigma, concealment and symptoms of depression explained variation in participants' histories of STIs. Results suggested that concealment partially mediated the relationship between stigma and depression and depression partially media… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
97
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 116 publications
(98 citation statements)
references
References 15 publications
1
97
0
Order By: Relevance
“…Poor mental health of LGBT individuals has been associated with illicit drug use, 39 sexually transmitted infections, 40,62 tobacco use, [41][42][43] and alcohol abuse. 12 Most of these associations have been identified in LGBT adolescents, although research on sexual minority women has found reduced mental health to be associated with poor health-related quality of life, 44 lack of exercise, 12 and poor general health.…”
Section: Discussionmentioning
confidence: 99%
“…Poor mental health of LGBT individuals has been associated with illicit drug use, 39 sexually transmitted infections, 40,62 tobacco use, [41][42][43] and alcohol abuse. 12 Most of these associations have been identified in LGBT adolescents, although research on sexual minority women has found reduced mental health to be associated with poor health-related quality of life, 44 lack of exercise, 12 and poor general health.…”
Section: Discussionmentioning
confidence: 99%
“…There are mixed findings regarding concealment and its link with both negative (e.g., Ayala & Coleman, 2000;Frost & Bastone, 2008;Frost, Parsons, & Nanin, 2007;Pachankis & Goldfried, 2006) and positive outcomes (Frable, Wortman, & Joseph, 1997). Studies have even indicated no relationship with health-related consequences (Kuyper & Fokkema, 2011;Lewis et al, 2003;McGregor et al, 2001;Oetjen & Rothblum, 2000).…”
Section: And Sense Of Belonging (Mccallummentioning
confidence: 91%
“…These domains included: knowledge of safe/unsafe sexual practices; 7 self-efficacy; 8,9 transgender-related stress and stigma; 10,11 coping; 12 health protective communication skills; 13 self esteem; 14 depression; 15 and social support. 16 We assessed acceptability through the following three questions about perceived helpfulness and effectiveness of the intervention: "The program helped me understand things that might cause me to engage in unhealthy behavior, like unsafe sex," "This program helped me create positive goals and feel better about my future," and "I would recommend the Life Skills intervention to other transgender women.…”
Section: Data Collectionmentioning
confidence: 99%